PELAKSANAAN KEGIATAN REFORMA AGRARIA MELALUI PROGRAM REDISTRIBUSI TANAH DI DESA CITOREK TIMUR KECAMATAN CIBEBER KABUPATEN LEBAK: Agrarian Reform Activities Through the Land Redistribution Program in Citorek Timur Village Cibeber District, lebak District - Trianassari, Tedy Kurniawan; Pandamdari, Endang (Faculty of Law, Universitas Trisakti, 2024)
Indonesia is reorganizing land tenure in a more equitable and equitable manner called Agrarian Reform. This activity was also carried out in Citorek Village. However, in its implementation there is a discrepancy between the implementation and the applicable laws and regulations. Therefore, the problem that arises is how the implementation of the land redistribution program in East Citorek Village is in accordance with Presidential Regulation No. 86 of 2018 and what obstacles exist during the implementation of the land redistribution program in East Citorek Village. The type of research method used is sociological jurisprudence, descriptive in nature, data sources are obtained through literature study and secondary data, data collection methods are carried out through literature study techniques, data analysis using qualitative methods and deductive inference. The conclusion of the research found that in its implementation, there are discrepancies regarding the subject of land redistribution recipients and at the implementation stage there are counseling activities that should be carried out at the planning stage. The obstacles to the implementation of land redistribution are found in the regulations, in the implementation and in the community.